The Estetika Penataan Artistik Film Sebelum Iblis Menjemput Ayat 2 Karya Timo Tjahjanto (2020) - Abdul Rohim; Fajar Aji; Dwi Haryanto (Program Studi Film dan Televisi Universitas Jember, 2023)
The application of artistic order in films needs to consider the aesthetic value. The artistic arrangement of a film is more influential if every detail can contribute to the aesthetic value that is enjoyed and accepted by the audience to support the story. Sebelum Iblis Menjemput Ayat 2 released on February 27, 2020. Sebelum Iblis Menjemput Ayat 2 movie is a follow-up story from Sebelum Iblis Menjemput movie which was released in 2018. This article discusses the aesthetics of the artistic arrangement in Sebelum Iblis Menjemput Ayat 2 movie by Timo Tjahjanto. This study uses Doeana's theory of film and television artistic order as the main theory, and A.A.M. Djelantik's aesthetic theory includes form, weight or content, and appearance is a supporting theory. The type of research used is a type of qualitative research using descriptive writing techniques. The results of the study are that the aesthetics of artistic arrangement in ritual scenes and climax scenes are depicted through the use of room settings that tend to be dark, the use of properties in the form of goat heads and ancient Greek mythology books, as well as the use of make-up, and clothing that shows the identity of each character.